Nutrition in the Bin: A Nutritional and Environmental Assessment of Food Wasted in the UK - Cooper, Karen A.; Quested, Tom E.; Lanctuit, Helene; Zimmermann, Diane; Espinoza-Orias, Namy; Roulin, Anne (Frontiers in Nutrition, 2018)
The UK currently has the most detailed, directly measured data for food wasted in the home. This includes information on the exact types of food wasted. These data allow calculation of the nutrients within that waste, as well as its environmental impact. The results progress the conversation beyond how much food is wasted or its energy content; it permits the implications for nutrition and sustainability to be assessed in detail. Data for UK household food waste were expressed as an average waste per capita for each type of food. Each food type was matched with an item (or group of items) from the UK Composition of Foods (7th Ed). The level of nutrients wasted was compared to UK Reference Nutrient Intakes (RNIs) for adult women (19–50 years, used as a proxy for general population requirements). The data were normalized into “nutrient days” wasted per capita per year, then into the number of complete diet days (for 21 nutrients plus energy). Results show that approximately 42 daily diets were discarded per capita per year. By individual nutrient, the highest losses were vitamin B12, vitamin C, and thiamin (160, 140, and 130 nutrient days/capita/year, respectively). For protein, dietary energy and carbohydrates, 88, 59, and 53 nutrient days/capita/year, respectively, were lost. Substantial losses were also found for under-consumed nutrients in the UK: calcium, which was mostly lost via bakery (27%) and dairy/eggs (27%). Food folate was mainly lost through fresh vegetables/salads (40%) and bakery (18%), as was dietary fiber (31 and 29%, respectively). Environmental impacts were distributed over the food groups, with wasted meat and fish the single largest contribution. For all environmental impacts studied, the largest contribution came from agricultural production. This paper shows that there are areas where interventions preventing food waste and promoting healthy eating could work together (e.g., encouraging consumption of vegetables or tackling overbuying, especially of unhealthy foods). Food manufacturers and retailers, alongside governments and NGOs, have a key role to minimize waste of environmentally impactful, nutrient-dense foods, for instance, by helping influence people’s behaviors with appropriate formulation of products, packaging, portioning, use of promotions, or public education.